Hemophagocytic lymphohistiocytosis complicating invasive pneumococcal disease: a pediatric case report - Mitsuru Tsuge; Machiko Miyamoto; Reiji Miyawaki; Yoichi Kondo; Hirokazu Tsukahara (BMC, 2020)
Abstract Background Hemophagocytic lymphohistiocytosis (HLH) is an infrequent but life-threatening disease due to excessive immune activation. Secondary HLH can be triggered by infections, autoimmune diseases, and malignant diseases. Streptococcus pneumoniae is a pathogenic bacterium responsible for invasive pneumococcal disease (IPD) such as meningitis and bacteremia. Although the pneumococcal conjugate vaccine (PCV) has led to reductions in IPD incidence, cases of IPD caused by serotypes not included in PCV are increasing. There are few reports of secondary HLH caused by IPD in previously healthy children. We herein report a rare case of a previously healthy boy with secondary HLH complicating IPD of serotype 23A, which is not included in the pneumococcal 13-valent conjugate vaccine (PCV-13). Case presentation An 11-month-old boy who had received three doses of PCV-13 was hospitalized with prolonged fever, bilateral otitis media, neutropenia and elevated C-reactive protein (CRP) levels. Blood culture on admission revealed S. pneumoniae, leading to a diagnosis of IPD. HLH was diagnosed based on a prolonged fever, neutropenia, anemia, hepatosplenomegaly, hemophagocytosis in the bone marrow, and elevated serum levels of triglycerides, ferritin, and soluble interleukin-2 receptor. He received broad-spectrum antibiotics and intravenous immunoglobulins for IPD and high-dose steroid pulse therapy and cyclosporine A for HLH; thereafter, his fever resolved, and laboratory findings improved. The serotype of the isolated S. pneumoniae was 23A, which is not included in PCV-13. Conclusions It is important to consider secondary HLH as a complication of IPD cases with febrile cytopenia or hepatosplenomegaly, and appropriate treatment for HLH should be started without delay.